Lessons from the European financial crisis - Marco Pagano (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
This paper distils three lessons for bank regulation from the experience of the 2009-12 euro-area financial crisis. First, it highlights the key role that sovereign debt exposures of banks have played in the feedback loop between bank and fiscal distress, and inquires how the regulation of banks' sovereign exposures in the euro area should be changed to mitigate this feedback loop in the future. Second, it explores the relationship between the forbearance of non-performing loans by European banks and the tendency of EU regulators to rescue rather than resolving distressed banks, and asks to what extent the new regulatory framework of the euro-area "banking union" can be expected to mitigate excessive forbearance and facilitate resolution of insolvent banks. Finally, the paper highlights that capital requirements based on the ratio of Tier-1 capital to banks' risk-weighted assets were massively gamed by large banks, which engaged in various forms of regulatory arbitrage to minimize their capital charges while expanding leverage. This argues in favor of relying on a set of simpler and more robust indicators to determine banks' capital shortfall, such as book and market leverage ratios.
urn:nbn:de:hebis:30:3-353097
Keywords: G01; G21; G28; G33; 330; bank regulation; euro; financial crisis; sovereign exposures; forbearance; bank resolution; bank capital requirements